Pregnancy planning and adaptation to motherhood among HIV-positive pregnant women (Portuguese Journal of Family Medicine and General Practice, 2012)
PREGNANCY PLANNING AND ADAPTATION TO MOTHERHOOD AMONG HIV-POSITIVE PREGNANT WOMEN Objectives: To analyse the influence of the planning of pregnancy on the adaptation to motherhood among HIV-infected wo- men compared to healthy pregnant women.Design: Observational study with assessments performed during the second trimester of pregnancy and 2 to 4 days postpar- tum.Population: Ninety-eight women including 47 HIV-positive pregnant women and 51 healthy pregnant womenSetting: Hospitais da Universidade de Coimbra: Área de Gestão Integrada de Saúde Materno-Fetal -Psychological Intervention Unit of of the Doctor Daniel de Matos Maternity Hospital and the Doctor Alfredo da Costa Maternity Hospital (Lisbon). Methods: The adaptation to motherhood was assessed by the administration of three self-report questionnaires designed to assess psychopathological symptoms (Brief Symptom Inventory), emotional reactivity (Emotional Assessment Scale), and qua- lity of life (WHOQOL-Bref). The association between the planning of pregnancy and adaptation to motherhood was analysed comparing HIV-positive pregnant women and healthy pregnant women. Inferential statistics were used with a significance le- vel of 0.05.Results: The results support our hypothesis that unplanned pregnancies are associated with worse adaptation in the transition to motherhood. This is greater among HIV-infected women. In the postpartum period, unplanned pregnancies were significan- tly associated with higher psychopathology, higher negative emotional reactivity, and poorer quality of life.Conclusions: Our findings highlight the importance the planning of pregnancy in the adjustment to pregnancy and the pos- tpartum period. These findings also stress the importance of the discussion of childbearing plans with HIV-infected women be- fore pregnancy.
Keywords: Family Planning; Adaptation; Psychological; Human immunodeficiency virus